How Competitive Is Irish Manufacturing? - Cerra, Valerie (IMF Working Papers; Working Paper, 2002)
Ireland has had significant competitiveness gains in the 1990s on the basis of the standard manufacturing unit labor cost-based measure of the real effective exchange rate. A handful of sectors mostly dominated by multinational companies have accounted for the bulk of value added in production. Their productivity gains have greatly contributed to Ireland's exceptional growth performance in the 1990s, which has earned it the nickname of "Celtic Tiger." However, these sectors represent a disproportionately smaller share of manufacturing employment, and competitiveness in employment-intensive sectors has been much weaker. This paper thus explores Irish competitiveness from the viewpoint of risks to employment.